Comparison of two ancient Egyptian Middle Kingdom statuettes from the Museo Egizio of Torino through computed tomographic measurements. (August 2022) - Vigorelli, Luisa; Re, Alessandro; Buscaglia, Paola; Manfredda, Nicole; Nervo, Marco; Cavaleri, Tiziana; Del Vesco, Paolo; Borla, Matilde; Grassini, Sabrina; Guidorzi, Laura; Lo Giudice, Alessandro
Highlights: X-ray imaging is widely applied for Cultural Heritage thanks to the non-invasive approach. Micro-computed tomography was carried out on two ancient Egyptian woodden statuette. A comparison between the results obtained on the two objects were performed. Information on the artistic technique and state of conservation was obtained. Differences and similarities in technical features of the statuettes were discovered. Abstract: X-ray Computed Tomography (CT) has a significant role as investigation tool not only in medical and industrial applications, but also in cultural heritage studies. One of the main reasons for such broad adoption of this method is its non-destructive capability to investigate the inner structure of precious and unique artefacts that would instead be damaged by traditional sampling procedures. Ordinary X-ray radiography is limited and gives only 2D images, while high-resolution X-ray CT imaging gives non-invasive access to three-dimensional (3D) information. This article focuses on the comparison of micro-CT results obtained from the analysis of two ancient Egyptian wooden statuettes representing offering bearers. The artefacts belong to the collection of the Museo Egizio of Torino as part of the funerary assemblage of Minhotep, discovered in the Asyut necropolis. For the analysis, an upgraded version of the X-ray imaging apparatus located in the Centro Conservazione e Restauro "La Venaria Reale" (CCR) was used, in order to reach a higher final resolution than the one already present and used at CCR. Thanks to this investigation, much information on the artistic technique was obtained and it was possible to highlight differences and similarities in the technical features of the two statuettes, acquiring elements to understand the specific contribution of micro-tomography in studying the finds and hypothesizing a common production method.